Serum NT‐proCNP levels increased after initiation of GH treatment in patients with achondroplasia/hypochondroplasia. (25th February 2016) - Kubota, Takuo; Wang, Wei; Miura, Kohji; Nakayama, Hirofumi; Yamamoto, Keiko; Fujiwara, Makoto; Ohata, Yasuhisa; Tachibana, Makiko; Kitaoka, Taichi; Takakuwa, Satoshi; Miyoshi, Yoko; Namba, Noriyuki; et al.
Summary: Objective: Serum amino‐terminal propeptide of C‐type natriuretic peptide (NT‐proCNP) levels have been proposed as a biomarker of linear growth in healthy children. The usefulness of NT‐proCNP in patients with achondroplasia (ACH)/hypochondroplasia (HCH) remains to be elucidated. The objective was to study whether serum NT‐proCNP level is a good biomarker for growth in ACH/HCH and other patients of short stature. Design: This was a longitudinal cohort study. Patients: Sixteen children with ACH (aged 0·4–4·3 years), six children with HCH (2·7–6·3 years), 23 children with idiopathic short stature (ISS) (2·2–9·0 years), eight short children with GH deficiency (GHD) (2·9–6·8 years) and five short children born small for gestational age (SGA) (2·0–6·6 years). Patients with ACH/HCH received GH treatment for 1 year. Measurements: Serum NT‐proCNP levels and height were measured. Results: NT‐proCNP levels positively correlated with height velocity in these short children ( P < 0·05, r = 0·27). NT‐proCNP levels inversely correlated with age in children with ISS alone ( P < 0·01, r = −0·55). Serum NT‐proCNP levels in patients with ACH/HCH were increased 3 months following the initiation of GH treatment ( P < 0·05). Height SDS gain during GH treatment for 1 year was positively correlated with the changes in NT‐proCNP levels after the initiation of GH ( P < 0·01, r = 0·72). Conclusion: Serum NT‐proCNP levels may be a good biomarker to indicate the effect of GH treatment on growth in patients with ACH/HCH at least in the first year and height velocity in short stature patients.